Integration of Digital Transformation, Management Accounting Practices, and Fraud Prevention in Micro, Small, and Medium-Sized Enterprises (MSMEs) - Novita Setianti; Agung Pratapa; Puji Lestari; Eliada Herwiyanti; Dewi Susilowati (Amkop Management Accounting Review (AMAR), 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face a digitalization paradox: despite the rapid adoption of digital technologies, vulnerability to fraudulent activities increases alongside weak internal controls. This study investigates the integrative role of digital transformation and Management Accounting Practices (MAP) in fraud prevention among MSMEs in the Banyumas region, Central Java. Grounded in the Resource-Based View (RBV), the Technology-Organization-Environment (TOE) Framework, and Fraud Triangle Theory, the study constructs a mediation model in which MAP serves as a mediator between digital maturity and fraud mitigation effectiveness. Primary data were collected from 136 respondents comprising MSME owners and managers through purposive sampling using a structured questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Results indicate that: (1) digital transformation positively and significantly influences MAP (β = 0.671); (2) MAP positively and significantly influences fraud prevention (β = 0.563); (3) digital transformation directly influences fraud prevention (β = 0.247); and (4) MAP mediates the relationship between digital transformation and fraud prevention with an indirect effect of 0.378. The overall model explains 63.9% of variance in fraud prevention (R² = 0.639). This study contributes theoretically and practically by demonstrating that digital transformation must be integrated with structured management accounting practices to create a secure and accountable financial ecosystem for MSMEs.